Initial growth of sunflower cultivar SYN045 under irrigation with saline stress (Research, Society and Development, 2020)
The objective is to analyze the behavior of the initial growth of the sunflower, to cultivate SYN045, influenced by different levels of salinity in the irrigation water. The work was implemented and conducted at the Educational Field Unit of the Agricultural Studies and Research Group in Caatinga - GEPAC at the Federal Institute of Bahia, Campus Serrinha, located in the municipality of Serrinha in the State of Bahia. The research consisted of four levels of saline water with five replicates each, with one plant per pot, totaling 20 plants. The treatments used with saline water were: S0 = 0.4; S1 = 2.2; S2 = 4.4 and S3 = 6.6 dS.m-1. To differentiate the saline treatments, NaCl, CaCl2.2H2O and MgCl2.6H2O were added, in the proportion of 7:2:1 to the supply water. The variables of stem height of the plant and Absolute Growth Rate of stem were analyzed. With the results obtained in the field, it is possible to affirm that the increase in salt concentrations in irrigation water negatively affects the growth and development of the sunflower cultivar SYN045.